Polls and Elections: The Chicago Record Poll and the Election of 1896. - Thies, Clifford F. (Presidential Studies Quarterly, 2018)
The Chicago Record poll of the presidential election of 1896 was an enormous, multistate mail survey. Unfortunately, its results were incredible. The newspaper attempted to correct the results, making perhaps the first ever attempt to deal with nonresponse bias, but did not have much success. Had responses been properly corrected for differences in response rate, the poll would have generated a satisfactory set of predictions.